Measuring Vulnerability in Grief: The Psychometric Properties of the Italian Adult Attitude to Grief Scale - Alessio Gori; Eleonora Topino; Pierluigi Imperatore; Alessandro Musetti; Julius Sim; Linda Machin (MDPI AG, 2023)
Although experiences of loss and the consequent grief are natural in human life, some individuals may have difficulty managing these events, to the point of developing significant impairment in their functioning in important life areas. Given this, the present research aimed to explore the psychometric properties of the Italian version of the Adult Attitude to Grief scale (AAG) to facilitate research on adult vulnerability to grief among Italian-speaking populations. A sample of 367 participants (Mage = 30.44, SD = 11.21; 78% females) participated in this research. A back-translation procedure was implemented to develop the Italian AAG. Then, participants completed the Italian AAG alongside a battery of other self-report psychometric scales in order to assess aspects of the construct validity of the AAG: the Forty-Item Defense Style Questionnaire, the Impact of Event Scale-Revised, and the Beck Depression Inventory-II. A bifactor structure was found to have the best fit to the data, supporting the possibility of using both the general factor (i.e., vulnerability) and three dimensions (i.e., overwhelmed, controlled, and resilient). Unlike the original version, the control dimension emerged as a "protective" factor in the Italian population, together with the resilient factor. Furthermore, results provided satisfactory indications of internal consistency and construct validity. In conclusion, the Italian AAG was shown to be a valid, reliable, quick, and easy-to-use scale that can be used both for research and clinical practice in the Italian context.